Analisa Debit Aliran Irigasi Saluran Induk Sawitto Terhadap Kebutuhan Air Sawah Di Kabupaten Pinrang - Ilham L; A Sulfanita; Andi Bustan Didi; Adnan Adnan (Pusat riset dan Inovasi Nasional, 2024)
This research aims to determine the available water discharge in the Sawitto Main Channel in Kab. Pinrang and the amount of discharge available at Benteng Dam and to find out whether the flowing discharge can meet the water needs of the Sawitto Main Canal Irrigation. In this research, primary and secondary data collection was carried out in the field and at the UPTD PSDA office in the Sadang River Region using quantitative descriptive research methodology. Data were analyzed using the Water Balanced method. The results of the research show that the water balance condition in the Sawitto irrigation area in Pinrang district is experiencing a surplus where the availability of water exceeds the amount of air flow required with the largest difference being in June where the availability of air flow is 510 m3/second, the air flow requirement is 18.43 m3/second, with a water difference of 491.57 m3/second and the smallest difference was in November 201 m3/second, the water discharge requirement was 61.53 m3/second with a difference of 139.47 m3/second.